TEACHING STUDENTS SPEAKING SKILL THROUGH FISHBOWL TECHNIQUE ON SUBJECT OF ENGLISH FOR TOURISM - Acep Haryudin; Aseptiana Parmawati (Jurnal Ilmiah P2M STKIP Siliwangi, 2019)
The ability to speak is the main basis that must be possessed by every student, especially for students who majored in English education. However, most problems in the process of teaching English are closely related to the ability to speak itself. The formulation of the problem in this study are; is there a significant improvement in speaking skills when applying the fishbowl technique to the English for Tourist Guide course? and What are the classroom situations and conditions when the fishbowl technique is applied in the learning process in the English for Tourist Guide course? Therefore, the long-term goal of this research is to produce learning theories that can be applied by lecturers without changing their roles but can optimize the creativity and ability of students in good English and in accordance with applicable language rules. This research method is quantitative research and the design used in this study is Classroom Action Research (CAR) which consists of several cycles with a sample of one class, namely class A3 2016 IKIP SIliwangi. The results and conclusions in this study are the sum of all student scores in the pre-test is 122, and the total score in session 1 is 154, while the score in session 2 is 187, after averaged, the scores obtained are 4.5 for the scores pre-test, 5,7. for the value of session 1, and 6.9 for the value of session 2 from the analysis made, it can be concluded that the results obtained have not demonstrated the success of Fishbowl learning conducted by lecturers / researchers. Looking at the comparison of initial values, the value of the first cycle and the value of the second cycle, there was a significant increase, namely from the average initial value of 4.5 rising in cycle I to 6.3 and in cycle II rising to 7.9 This increase could not underestimated because this increase in value is from the maximum efforts carried out by researchers for the sake of improving the quality of education and the advancement of education, especially in English Language Study Program IKIP Siliwangi.